The Linear Vibrational Behavior of Thick Plates Including the Effects of Shear and Rotary Inertia - Jweeg, Muhsin J.; Hussain, Ahmdd A.; Al-Sada, Wisam Abed (Nahrain University College of Engineering Journal, 2010)
In this work, a suggested analytical solution for static and dynamic analysis of (fiber-reinforced) composite laminated thick plate is developed by using the singlelayer theory and first-order shear deformation theory (FSDT) theory. The dynamic analysis for equations of motion for those theories is presented and solved byusing the modal analysis method of forced vibration. A computer program was built for this purpose for anti-symmetric crossply and angle-ply and simply supported thick laminated plate and the developed equations are solved by using (MATLAB V.7) program. The numerical solution by using finite-element technique is also adopted using (ANSYS V5.4) package, to compare the analytical results. Both above approaches use (FSDT) and include the effect of shear deformation and rotary inertia. The results are the deflection, stress in each layer and (through thickness) interlaminar shear stress for thick laminatedplates with different boundary conditions subjected to the static and dynamic loading conditions. The results presented show the effect of plate thickness-to-length ratio (h/a), aspect ratio (a/b), number of layers (N), the degree of orthotropy ratio (E1/E2), fiber orientation, boundary conditions, lamination scheme, and the effect of shear deformation and rotary inertia on the thick laminated plate.